Pre-Melting-Assisted Impurity Control of β-Ga2O3 Single Crystals in Edge-Defined Film-Fed Growth - A-Ran Shin; Tae-Hun Gu; Yun-Ji Shin; Seong-Min Jeong; Heesoo Lee; Si-Young Bae (Nanomaterials)
This study reveals the significant role of the pre-melting process in growing high-quality (100) β-Ga2O3 single crystals from 4N powder (99.995% purity) using the edge-defined film-fed growth (EFG) method. Among various bulk melt growth methods, the EFG method boasts a fast growth rate and the capability of growing multiple crystals simultaneously, thus offering high productivity. The pre-melting process notably enhanced the structural, optical, and electrical properties of the crystals by effectively eliminating impurities such as Si and Fe. Specifically, employing a 100% CO2 atmosphere during pre-melting proved to be highly effective, reducing impurity concentrations and carrier scattering, which resulted in a decreased carrier concentration and an increased electron mobility in the grown Ga2O3 single crystals. These results demonstrate that pre-melting is a crucial technique for substantially improving crystal quality, thereby promising better performance in β-Ga2O3-based device applications.